Do antenatal maternal and paternal depression levels affect emotional availability during mother-child and father-child interactions? - Trentini, Cristina; Dentale, Francesco; Tambelli, Renata (Psychology Hub, 2021)
This study determined the predictive value of antenatal maternal and paternal depressive symptoms in emotional availability (EA) during mother-child and father-child interactions. A self-reported measure of depression was administered to 50 couples of primiparous parents during the seventh/eighth month of pregnancy, and an observational system was applied to assess parent-child EA when the children were aged 7 and 9 months. To disentangle the contributions from the mother and fathers, 2 moderated regression models were tested separately for maternal and paternal EA, with maternal and paternal depressive symptoms and their interaction as predictors and the partners’ EA and age as controls. In the first model, maternal depressive symptoms (beta = -.32, p = .01) and paternal EA (beta = .57, p <.01) had a significant effect, and there was a significant interaction between maternal and paternal depressive symptoms (beta = -.24, p = .03). No significant effects emerged for paternal depressive symptoms or maternal age. A simple-slope analysis of the interaction showed that for high levels of depression in fathers (+1 SD), the relationship between maternal depressive symptoms and maternal EA was negative and significant (r = -.56, p = .005), whereas for low levels (-1 SD), this relationship tended to dissipate. Regarding the second model, no significant effects were found for maternal or paternal depressive symptoms or their interaction. Overall, the results suggest that high levels of maternal depressive symptoms during pregnancy impairs the development of adequate maternal EA. This risk increases when maternal and paternal depressive symptoms are high, implicating the importance of the relationship between parents. These effects were not observed for paternal EA.